2011
DOI: 10.1371/journal.pmed.1001127
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Medical Male Circumcision: An Introduction to the Cost, Impact, and Challenges of Accelerated Scaling Up

Abstract: Catherine Hankins, Steven Forsythe, and Emmanuel Njeuhmeli provide an overview of the “Voluntary Medical Male Circumcision for HIV Prevention: The Cost, Impact, and Challenges of Accelerated Scale-Up in Southern and Eastern Africa” Collection, calling for leadership and vision to help halt the HIV epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…Several modeling studies found that the longterm population-level impact of widespread implementation and scale-up of voluntary medical male circumcision (VMMC) services will result in substantial reductions in HIV incidence for both men and women [8][9][10][11][12]. As a result, ten of the fourteen high-priority countries are actively engaged in national VMMC program scale-up [13][14][15]. However, questions remain about whether the promotion of VMMC as an HIV prevention intervention will translate into a decline in HIV incidence in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Several modeling studies found that the longterm population-level impact of widespread implementation and scale-up of voluntary medical male circumcision (VMMC) services will result in substantial reductions in HIV incidence for both men and women [8][9][10][11][12]. As a result, ten of the fourteen high-priority countries are actively engaged in national VMMC program scale-up [13][14][15]. However, questions remain about whether the promotion of VMMC as an HIV prevention intervention will translate into a decline in HIV incidence in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In female partners, circumcision was found to reduce trichomonas, bacterial vaginosis, HPV and genital ulceration 14. One trial reported that MMC did not affect HIV acquisition in female partners over a period of two years,15 but modelling suggests that if male HIV prevalence is reduced by MMC, it will reduce female exposures and, thus, indirectly reduce infection in women 16 17…”
Section: Introductionmentioning
confidence: 99%
“…The agency set a goal of providing MMC to 20.3 million men in 14 priority southern and eastern African countries by 2015 in order to achieve 80% coverage, with a further 8.42 million procedures between 2016 and 2025 to maintain the 80% coverage 16 19. It is estimated that if targets are achieved, it could avert ∼3.36 million new HIV infections by 2025 at a cost of US$2 billion, producing a net saving of ∼US$16.51 billion by averted treatment and care costs 19…”
Section: Introductionmentioning
confidence: 99%
“…Results from simulations and meta-studies support the claim that male circumcision is one of the most cost-effective HIV prevention interventions (Joint United Nations Program on HIV/AIDS, 2009;WHO, 2011;Hankins et al, 2011;Nagelkerke et al, 2007;White et al, 2008;Williams et al, 2006). The most recent simulations suggest that scaling up medical male circumcision to 80 percent coverage in priority countries could avert approximately 22 percent of HIV infections through 2025, resulting in a net savings of US$16.51 billion .…”
Section: Introductionmentioning
confidence: 74%